Economic development and heritage of the Philippines proposed learning units for Social Studies III - Mendoza, Martina M. 1949- (1979)
The purpose of this study was to prepare learning units on the concepts of economic development and heritage. The ideas gleaned from literature on social studies led the researcher to make the following conclusions: the problem of lack of instructional materials was strongly felt by the educational planners, teachers and students; the new social studies objectives were geared towards the attainment of the national development goals of the country; the new social studies is still a new curricular revision up to the present; and the content of Philippine social studies textbooks is multi- and interdisciplinary
Vita.
Thesis (M.A. Social Studies Education)--University of the Philippines, Diliman.
Keywords: Social sciences -- Study and teaching -- Philippines; Teaching -- Philippines -- Aids and devices; Philippines -- History -- Study and teaching